Assessment of Tumor Response to Neoadjuvant Chemotherapy in Breast Cancer Using MRI and 18F FDG PET/CT - Reem Yusuf AlBuainain; Fatema Yusuf Bunajem; Hussain Adnan Abdulla (European Journal of Breast Health)
Objective: Neoadjuvant chemotherapy (NACT) has been the primary treatment method for patients with local advanced breast cancer. A pathological complete response (pCR) to therapy correlates with better overall disease prognosis. Magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT) have been widely used to monitor the response to NACT in breast cancer. The aim of this study was to assess tumor response to NACT by MRI and PET/CT, to determine which imaging modality is more accurate in detecting tumor response post NACT in breast cancer. Materials and Methods: A retrospective review of our database revealed 34 women with breast cancer thathad MRI and PET/CT performed prior to and after NACT, followed by definitive surgery. For response assessment, we calculated the difference in maximum diameter of the tumor in MRI and difference in standard uptake values in PET/CT. The correspondence rate between the imaging modalities and pCR were calculated. For the prediction of pCR, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy where analyzed. Results: The assessment of tumor response to NACT showed 11cases with pCR (32%), 15 pathological partial response (44%) and eight pathological no response (24%). The correspondence rate between MRI and pathological response was 50% (17/34), compared to 65% (22/34) for PET/CT. For prediction of pCR, MRI showed higher specificity compared to PET/CT (78.2% vs. 73.9%, p = 0.024), while the accuracy of PET/CT was significantly higher (79.4% vs. 70.5%, p = 0.004). PET/CT also had a higher NPV compared to MRI (94.4% vs. 78.2%, p = 0.002). There were no differences in terms of sensitivity and PPV between MRI and PET/CT. Conclusion: Compared to MRI, PET/CT was more likely to correlate with the pathological response after NACT. For the prediction of pCR, PET/CT proved to be a more accurate imaging modality to monitor response after NACT than MRI.